Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Kinerja Guru di SD Negeri Sapugara Kecamatan Brang Rea Kabupaten Sumbawa Barat Tahun Pelajaran 2019/2020 - Zainuddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This PTS discusses the managerial competence of school principals in improving teacher performance at SD Negeri Sapugara, Brang Rea District, West Sumbawa Regency, motivated by the important role of the principal in improving teacher performance, implementing school quality and at the same time in improving the quality of learning management, because of the steps a school organization controlled by a principal. This study is intended to answer the problem of how the principal's leadership is viewed from managerial competence in improving teacher performance in SD Negeri Sapugara, Brang Rea District, West Sumbawa Regency. This type of research is qualitative research. Methods of data collection using interviews, observation and documentation. Data analysis using qualitative descriptive analysis. The results show that in the context of managerial competence, the principal of SD Negeri is able to prepare school plans for various levels of planning, develop school organizations according to needs, lead schools in order to optimize school resources, have the right strategy to improve the performance of educational personnel. at his school. Creating a conducive school climate, providing advice to school residents, encouraging all teachers, and implementing interesting learning models. It is human nature, besides the advantages there are also disadvantages, namely the Principal of SD Negeri because of his too discipline, sometimes in certain situations he is active in filling the lesson hours which are actually a portion of the teacher concerned. This condition gives the impression that the principal's level of trust in teachers is lacking